Association of milk production and udder type traits with polymorphism of phosphorylase kinase regulatory subunit alpha-2 gene in Sahiwal cattle - TOGLA, OSHIN; DEB, S M; KADYAN, SAGAR; KUMAR, SUSHIL; NANDHINI, P B; MUKHERJEE, ANUPAMA (The Indian Journal of Animal Sciences, 2021)
The study was conducted in Sahiwal cattle in tropical region in the Indian sub-continent where the production of dairy animals is yet to be optimised. The present investigation was executed to identify SNPs in PHKA2 gene and to explore its effect on udder type and milk production traits. The study was based on the hypothesis that the PHKA2 gene has highly variable exons that could be related with udder traits and eventually milk production. PHKA2 gene regulates glycogen phosphorylase a, a catalyst in breakdown of glycogen. Milk production traits were recorded; 9 udder type, 5 teat type and 8 visual traits were measured for 100 animals. Five highly variable targeted regions of PHKA2 gene were amplified using PCR and sequenced. The association analysis was carried out using general linear model (SAS) to study the fixed effect of genotype on studied traits. The synonymous type SNP g.124556852C>T was found for the first time in Sahiwal cattle and possibly associated with udder type traits. The genotypic frequencies with respect to targeted loci g.124556852C>T indicated that homozygote CC (0.58) were highest in our resource population. The chi-square 2 test showed an agreement to Hardy–Weinberg equilibrium. The association analysis revealed significant association of genotypes with udder width, udder balance and 305 days milk yield. The attempt to find significant association with the visual udder traits was also done, however no significant alliance was observed. Homozygote CC animal were desirable as they favoured the selection of animal with superior udder width, udder balance and 305 day’s Milk Yield values.